Governing Juana: Madness and Manipulation of Power in Three Spanish American Plays on Juana la Loca - López, Kimberle S.; Marino Segura, Angela (Latin American Theatre Review, 2008)
This article examines the representation of Juana of Castile in three twentieth-century Spanish American plays — Zavalía’s El corazón extraviado — (Argentina, 1957), Sabido’s Falsa crónica de Juana la Loca (Mexico, 1985), and Rueda’s Retablo de la pasión y muerte de Juana la Loca (Dominican Republic, 1996) — that portray the queen sympathetically as the victim of elaborate plots to usurp her authority. While the plays expose her madness as a pretext used by her father King Fernando and her son Emperor Carlos V to confine her for nearly half a century in the palace of Tordesillas, they do not deny the basic premises of the official history of “Juana la loca.” Thus, the captive queen is represented on stage as not only unable to govern Spain, but also as unable to control herself, leading others to “govern Juana.” (KL and AMS, Article in English)